(untitled) (Modern education and development, 2024)
Achieving success in family education Sharing of experiences on family education, active involvement of parents in educational work It’s also about doing. Each parent should deeply understand their duties and responsibilities in family education And we, as parents, if we can give them the right education, we will see the perfection of this. For our country, we need to raise children who will benefit the knowledge-based society.